Quaternary ammonium compounds in hypersensitivity reactions - Peyneau, Marine; de Chaisemartin, Luc; Gigant, Nicolas; Chollet-Martin, Sylvie; Kerdine-Römer, Saadia (Frontiers in Toxicology, 2022)
Quaternary ammonium compounds (QAC) are commonly used disinfectants, antiseptics, preservatives, and detergents due to their antibacterial property and represent the first used biocides before phenolic or nitrogen products. Their common structure consists of one or more quaternary ammonium bound with four lateral substituents. Their amphiphilic structure allows them to intercalate into microorganism surfaces which induces an unstable and porous membrane that explains their antimicrobial activity towards bacteria, fungi, and viruses. QAC are thus found in many areas, such as household products, medicines, hygiene products, cosmetics, agriculture, or industrial products but are also used in medical practice as disinfectants and antiseptics and in health care facilities where they are used for cleaning floors and walls. QAC exposure has already been involved in occupational asthma in healthcare workers or professional cleaners by many authors. They also have been suggested to play a role in contact dermatitis (CD) and urticaria in workers using cosmetics such as hairdressers or healthcare workers, inciting reglementary agencies to make recommendations regarding those products. However, distinguishing the irritant or sensitizing properties of chemicals is complex and as a result, the sensitizing property of QAC is still controverted. Moreover, the precise mechanisms underlying the possible sensitization effect are still under investigation, and to date, only a few studies have documented an immunological mechanism. Besides, QAC have been suggested to be responsible for neuromuscular blocking agents (NMBA) sensitization by cross-reactivity. This hypothesis is supported by a higher prevalence of quaternary ammonium (QA)-specific IgE in the professionally exposed populations, such as hairdressers, cleaners, or healthcare workers, suggesting that the sensitization happens with structurally similar compounds present in the environment. This review summarizes the newest knowledge about QAC and their role in hypersensitivities. After describing the different QAC, their structure and use, the most relevant studies about the effects of QAC on the immune system will be reviewed and discussed.